Pengaruh perceived organizational support terhadap work engagement dimediasi oleh regulatory focus ibu bekerja pada masa pandemi Covid-19 - Tuti Rahmi; Hendriati Agustiani; Diana Harding; Efi Fitriana (Jurnal Kajian Manajemen Bisnis, 2021)
The study examined the effect of perceived organizational support on work engagement with regulatory focus as a mediator. Regulatory focus consists of prevention focus and promotion focus which is a multi-dimensional construct so that every dimension was treated as a variable. The approach of this research was quantitative, with a survey method. The distribution of the research scale was carried out online. The research participants were 83 working mothers as civil servants in the local government of the City of Bukittinggi. Data analysis was performed using structural equation modeling with SmartPLS v.3.3.3 Software. The results showed that there was an effect of perceived organizational support on work engagement. However, there is no evidence of mediation by regulatory focus between the variables of perceived organizational support and work engagement. Keywords: Perceived organizational support; work engagement; regulatory focus;  working mother